Exploring Edible Bird Nest's Potential In Mitigating Wi-fi's Impact On Male Reproductive Health - Sofwatul Mokhtarah Maluin; Farah Hanan Fathihah Jaffar; Khairul Osman; Aini Farzana Zulkefli; Mohd Farisyam Mat Ros; Siti Fatimah Ibrahim (John Wiley & Sons, Inc, 2024)
Indexed by WOS/ Scopus